Viral isolates in pediatric ventilator-associated pneumonia - Bhawani Shankar Parihar; Ruchi Agrawal; Vijendra Kumar Garg; Jagdish Singh; Alok Kumar Goyal; Raj Kumar Gupta; Sunil Gothwal (Wolters Kluwer Medknow Publications, 2022)
Introduction: Although ventilator-associated pneumonia (VAP) mostly has bacterial etiology, many cases have viral etiology. The present study aimed at determining the proportion of viral VAP and any associated factors and identifying the viral isolates in pediatric VAP. Materials and Methods: A descriptive observational study was conducted at pediatric intensive care unit of tertiary referral center including 120 VAP cases aged 1-18 years. Endotracheal aspiration samples from these patients were tested for viral etiology. Results: Most VAP cases were males (66.7%). Virus was isolated in 14.2% of cases of VAP. Human adenovirus (29%), respiratory syncytial virus (29%), and herpes simplex virus (24%) were the most common viruses identified. Viral VAP was significantly associated with age, primary disease, and total leukocyte count. Neutrophil count decreased and lymphocyte count increased significantly after viral VAP. Conclusion: Viral etiology should be considered in VAP patients, especially in patients not responding to antibiotics as proper diagnosis and timely initiation of appropriate antiviral could be lifesaving. Prevalent viruses may vary geographically; hence, hospitals should try to identify the common viruses causing VAP in their settings to guide appropriate battery of tests and antiviral drugs.